Scaling Roadmap: Advancing User-centric Bundled Climate Information (CIS) and Digital Agro-Advisory Services (CSA) in Ethiopia - Ewell, Hanna; Rettie, Fasil; Ndour, Adama; Makonnen, Brook T.; Ambaw, Gebermedihin; Solomon, Dawit; Girvetz, Evan (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Key messages - Bundled CIS+CSA converts forecasts into timely, actionable advisories, inputs, and services—reducing climate risk, improving decisions, and raising productivity and incomes for diverse Ethiopian smallholders nationwide. - Lersha–CIMMYT model delivers biweekly voice/SMS advisories; links mechanization, inputs, credit, insurance, and markets; leverages agents, cooperatives, and meteorological services to reach women, youth, and non-literate farmers. - Responsible scaling: strengthen forecasts and localization; integrate with extension, finance, policy; diversify revenues; embed inclusion safeguards—building resilient, sustainable CSA/CIS ecosystems nationwide.